Evolution, Transmission, and Pathogenicity of High Pathogenicity Avian Influenza Virus A (H5N8) Clade 2.3.4.4, South Korea, 2014–2016 - Baek, Yoon-Gi; Lee, Yu-Na; Park, Yu-Ri; Chung, David H.; Kwon, Jung-Hoon; Si, Young-Jae; Heo, Gyeong-Beom; Lee, Youn-Jeong; Lee, Dong-Hun; Lee, Eun-Kyoung (Frontiers in Veterinary Science, 2022)
During 2014–2016, clade 2.3.4.4 H5N8 high pathogenicity avian influenza virus (HPAIV) caused the largest known avian influenza epidemic in South Korea. Based on data from earlier H5N8 outbreaks, primitive H5N8 virus in South Korea was classified into five subgroups: C1, C2, C3, C4, and C5. The present study investigated the pathogenic and molecular epidemiologic characteristics of H5N8 viruses obtained from 388 cases of poultry farms and 85 cases of wild bird infections in South Korea during 2014–2016. Representative viruses of subgroups C1, C2, and C4 showed significant pathobiological differences in specific pathogen-free (SPF) chickens, with the H1731 (C1) virus showing substantially lower infectivity, transmissibility, and pathogenicity than the H2102 (C2) and H1924 (C4) viruses. Full genome sequence analysis showed the number of mutations that significantly increased in domestic duck-origin H5N8 HPAIVs compared to the viruses from gallinaceous poultry. These differences may have been due to the long-term circulation of viruses in domestic duck farms. The same mutations, at positions 219 and 757 of PB1, independently evolving in the C0, C1, and C2 subgroups may have been positively selected, resulting in convergent evolution at the amino acid level. Bayesian discrete trait phylodynamic analysis (DTA) indicated multiple introductions of H5N8 HPAIV from wild birds into domestic poultry in various regions in South Korea. Following initial viral introduction into domestic duck farms in the western part of Korea, domestic ducks played a major role in viral transmission and maintenance. These findings highlight the need for continued genomic surveillance and pathobiological characterization of HPAIV in birds. Enhanced biosecurity in poultry farms should be implemented to prevent the introduction, maintenance, and spread of HPAIV.